An Exploration of the Views of Turkish EFL Instructors on Pronunciation Teaching - Bayram, Selçuk (Technium Social Sciences Journal, 2021)
The aim of this study was to investigate the views of Turkish EFL instructors in higher education institution on English pronunciation teaching. The study was conducted with 156 instrcutors working at English preparatory programs in various foundation universities in Istanbul. The research was conducted with a mixed method approach. Quantitative data was gathered by means of a questionnaire; and semi structured interviews were carried out to gather qualitative data. The results of the study shed light on the perspectives of Turkish EFL instructors on pronunciation teaching and their pronunciation teaching practices. The general tendency of the participants was slightly positive in terms of the importance attached to pronunciation teaching and significant differences were found between pronunciation teaching practices and taking phonology classes and years of experience. The analysis of the interview also supported the questionnaire results regarding views of instructors on pronunciation. In addition, the results revealed that the instructors in the study focus on segmental features, mostly using repetition and exercises limited to the course books they use while teaching pronunciation. The results also revealed that instructors needed education on pronunciation and pronunciation teaching.